ANALISIS PENGARUH KEPEMILIKAN MANAJERIAL, JUMLAH RAPAT KOMITE AUDIT, PROFITABILITAS, DAN KUALITAS AUDIT TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017--2019) - Laurentia Jessica Cecilia; Julianti Sjarief (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2022)
This research aimed to examine the influence of managerial ownership, the number of audit committee meetings, profitability, and audit quality on firm value. The population in this study was taken from manufacturing listed companies on the Indonesia Stock Exchange in 2017-2019. Based on the purposive sampling method with some criteria applied, 101 companies could be used as samples. The analytical methods used in this research are descriptive statistical analysis and multiple linear regression analysis and processed using the SPSS version 26.0 program. This study showed that managerial ownership does not affect firm value. The number of audit committee meetings has no effect on firm value. Profitability has a positive effect on firm value. The audit quality has a positive effect on firm value.